Early visual and neuro-development in preterm infants with and without retinopathy. (September 2020) - Ricci, Daniela; Lucibello, Simona; Orazi, Lorenzo; Gallini, Francesca; Staccioli, Susanna; Serrao, Francesca; Olivieri, Giorgia; Quintiliani, Michela; Sivo, Serena; Rossi, Valeria; Leone, Daniela; Ferrantini, Gloria; et al.
Abstract: Background: Retinopathy of prematurity (ROP) is often associated with visual impairment and multiple developmental disabilities. Aims: As most of the previous studies include infants with brain lesions, that can determine visual impairment per se, a cohort of low neurological risk preterm infants without ROP and with various degree of severity of ROP was assessed in order to establish visual and neurodevelopmental outcome. Study design: Preterm infants born at <31 weeks gestation, without major brain lesions, underwent visual function assessment at 1 year corrected age and neurodevelopmental assessment at 2 years corrected age. Subjects: One hundred and five infants were included in the study: 42 infants did not develop ROP, 7 reached stage 1 in zone 2 ROP, 37 reached prethreshold (untreated) type 2 ROP. The remaining 19 infants were classified as type 1 ROP. Outcome measures: Visual function (including fixing, tracking, visual acuity, visual field, attention at distance and nystagmus) were assessed at 12 months corrected age and Griffiths Scales at 2 years corrected age. Results: The severity of ROP was strongly correlated ( p < 0.001) with both visual function at 1 year and neurodevelopment at 2 years. Similarly, the presence of nystagmus was also strongly correlated with visual and neurodevelopmental sequelae. Conclusions: Infants with no or milder retinopathy showed normal visual function at 1 year and neurodevelopment at 2 years. Infants who underwent treatment more frequently showed abnormal results on several aspects of visual function. Presence of nystagmus appeared to increase the risk for abnormal visual function and neurodevelopmental outcome. Highlights: Infants with retinopathy of prematurity present a high risk of visual impairment and multiple developmental disabilities. No study has so far investigated early visual function and neurodevelopment in low neurological risk infants with different stages of ROP. There is a strong correlation between severity of ROP and both visual function at 1 year and neurodevelopment at 2 years. In infants with more severe ROP, presence of nystagmus was strongly correlated with visual and neurodevelopmental sequelae.